Overcoming barriers in continuous glucose monitoring: Challenges and future directions in diabetes management - Hung‐Chun Chen; Yi‐Hsuan Lai; Yi‐Der Jiang (Journal of Diabetes Investigation)
ABSTRACT Recent updates on the efficacy of continuous glucose monitoring (CGM) and a critical examination of the current challenges in its implementation were summarized. The barriers to widespread adoption of this technology should be addressed, considering the impact of different cultural contexts. The strategies to overcome these obstacles and the benefits of CGM for future glucose management will be discussed.